Biomass Morphology Subjected to Different Chemical Treatment - Norsuzailina, Mohamed Sutan; Siti Masjida, Mazlan; Siti Noor Linda, Taib; Teo, Delsye Ching Lee; Alsidqi, Hasan; Siti Kudnie, Sahari; Khairul Anwar, Mohamad Said; Habibur Rahman, Sobuz (EDP Sciences, 2018)
A growing interest of sugarcane bagasse fibre composite has been observed in recent years due to its attractiveness properties such as low specific weight, renewable source and producible with low investment at low cost. However, these materials have a low interfacial adhesion between fibre and matrix which lead to reduction in certain mechanical properties of the composite. To overcome this problem, studies show that certain chemical treatments on the surface of the fibres are some alternatives that significantly increase the adhesion reinforcement/matrix, in some cases improving its mechanical properties. The objective of this study was to evaluate the effect of different type of chemical treatment which are alkali and acid treatment on sugarcane bagasse fibre surface morphology. Seeking to improve the adhesion fibre matrix, the fibre has been treated with 5% of NaOH and 5% of HCL solution with added of bagasse fibre used in the range of 0% to 3% of cement weight respectively. Through SEM investigation, it is confirmed that chemical treatment helps to remove hemicelluloses from raw bagasse fiber as well as improved fibre matrix adhesion.